Association between sedentary time and sleep quality based on the Pittsburgh Sleep Quality Index among South Korean adults - Sung Hoon Jeong; Bich Na Jang; Seung Hoon Kim; Gyu Ri Kim; Eun-Cheol Park; Sung-In Jang (BMC, 2021)
Abstract Background Sleep problems increase the risk of premature illness and death. We evaluated the association between sedentary time and sleep quality among South Korean adults. Methods The data of adults (aged ≥ 19 years) from the 2018 Korea Community Health Survey were analyzed. Sedentary time, which included hours spent sitting or lying down daily, was categorized into four standardized groups. Poor sleep quality was defined using the global cutoff point (> 5 points) of the Pittsburg Sleep Quality Index. Multiple logistic regression analyses were performed to identify the association between sedentary time (≤ 3.9, 4.0-5.9, 6.0-7.9, and ≥ 8 hours /day) and sleep quality, by sex. Results Of the 224,118 participants, 35,784/100,454 men (35.6%) and 58,271/123,664 women (47.1%) had poor sleep quality. Compared with ≤ 3.9 h/day, sedentary times 4.0-5.9, 6.0-7.9, and ≥ 8 h/day were associated with worse sleep quality among men (odds ratio [OR]: 1.12, 95% confidence interval [CI]: 1.08-1.16; OR: 1.19, 95% CI: 1.14-1.25; OR: 1.30, 95% CI: 1.25-1.34, respectively) and women (OR: 1.06, 95% CI: 1.03-1.10; OR: 1.12, 95% CI: 1.08-1.16; OR: 1.22, 95% CI: 1.18-1.26, respectively). In subgroup analyses of sleep quality, subjective sleep quality, latency, disturbance, use of sleeping medication, and daytime dysfunction showed a strong dose-response relationship with increasing sedentary time in both sexes. Conclusions Regardless of sex, the longer the sedentary time, the stronger the association with poor sleep quality. Nationwide efforts are required to recommend standards for sedentary time and develop evidenced-based healthy behavior guidelines.